Aspek Hukum Pelaksanaan Pengujian Kelayakan Angkutan Bermotor; (Studi Kasus Di Unit Pelaksana Teknis Pengujian Kenderaan Bermotor, Terminal Pinang Baris Medan) - Harahap, Romulhan; Ginting, Budiman; Sikumbang, Jusmadi; Jamilah, Jamilah (Universitas Medan Area, 2020)
Transportation Agency is an organization that serves to held public services in road freight traffic. One of the programs the Department of Transportation that is the setting of public transport (people) through the testing of motor vehicles. Given the need for transport is a top priority in fulfilling the needs of daily life - a good day for work, school, college, and the other, the number of accident victims bring people, besides the risk of air pollution was inevitable. It was all no existence apart from motor vehicles both for public transport and private interests.